Comparison of Urea and Creatinine Levels in Lipemic Serum and Lipemic Serum Treated with Alpha-Cyclodextrin - Siti Ramadhani; Vitra Missi Agatha Agatha; Riri Safitri (Medistra Medical Journal (MMJ), 2026)
Background: Turbid (lipemic) serum is usually caused by an increase in lipoprotein levels so that turbidity can be clearly seen by the eye. The accumulation of lipoprotein particles causes lipemia in serum, but not all types of lipoproteins. The largest particles, namely chylomicrons with a size of 70-1000 nm, are the main cause of turbidity in serum samples. However, the accumulation of small particles, high density lipoprotein (HDL), low density lipoprotein (LDL) does not produce lipemic serum. Objective: To determine the differences in the results of the examination of urea creatinine levels in lipemic serum and lipemic serum given alpha cyclodextrin, and to determine how to properly handle lipemic serum.  Method: The type of research used in this method is a quantitative experiment with a one group pre and post test design plan. one group pre and post test design is quasi experimental. Results: normality test results show that the data is not normally distributed because the sig value. 0.05, then the research continued with the Friedman's ANOVA test. In the Friedman's ANOVA analysis carried out, the Asyms value was obtained. sig. (0.201) 0.05 Conclusion: So it can be concluded that there is no significant difference between lipemic serum and lipemic serum treated with alpha cyclodextrin in checking urea and creatinine using a chemical analyzer. From the analysis obtained through the Friedman ANOVA test, a sig value of 0.05 was obtained, which means there was no difference in the urea creatinine value in lipemic serum with lipemic serum that was given alpha cyclodextrin. Alpha cyclodextrin can be useful for handling lipemic samples, because alpha cyclodextrin is ale to detect lipids that cause lipemic